Finite element analysis for deeply buried concrete pipes in proposed imperfect trench installations with expanded polystyrene (EPS) foams. (15th June 2019) - Kang, Junsuk
Graphical abstract: Highlights: The proposed imperfect trench installation (ITI) approach could significantly reduce longitudinal stresses. The earth loads in ITI were found to be highly affected by soil properties. Imperfections in the bottom soft zone could induce higher contact pressures and shear stresses on buried pipes. Loosened sidefills in ITI produce higher longitudinal stresses associated with bending moments. Abstract: The objective of this study was to evaluate the performance of imperfect trench installations incorporating a soft material zone for buried concrete pipes. Traditionally, imperfect trench installations locate highly compressible lightweight materials such as expanded polystyrene foams, baled hay or straw above buried pipes in order to induce positive soil arching without trenches and hence reduce vertical top pressure and horizontal pressure. However, bottom pressure is not significantly reduced due to the additional downward shearing forces induced by transferring top pressure to the adjacent sides. Previous FE models that take account of plane strain elements suggest that soft zones surrounding pipes can markedly reduce bottom pressure, as well as the top and lateral pressures, but these models have not yet been validated by field tests and there have also been difficulties in evaluating the longitudinal behaviors of pipes. This study revisited the proposed use of soft zones using three-dimensional finite element analyses and validated the modeling methodologies using Valsangkar's field tests. The results confirm that soft zones are a highly effective way to reduce the surrounding pressures on deeply buried concrete pipes, and the new finite element models presented here successfully overcome the limitations of the previous plane strain approach.